2017
DOI: 10.1002/2017jc012691
|View full text |Cite
|
Sign up to set email alerts
|

Bay of Bengal salinity stratification and Indian summer monsoon intraseasonal oscillation: 1. Intraseasonal variability and causes

Abstract: The huge freshwater flux of the Indian summer monsoon (ISM; May–October) gives rise to strong salinity stratification in the Bay of Bengal (BoB), causing a shallow mixed layer and a thick barrier layer, which potentially affects intraseasonal oscillations of the monsoon (MISOs). In this study, intraseasonal variability of the mixed‐layer depth (MLD) and barrier layer thickness (BLT) is investigated using in situ observations from Argo floats and moored buoys and an ocean general circulation model (OGCM). The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 89 publications
1
39
0
Order By: Relevance
“…However, the EKE patterns in the NoISO (Figure b) and NoSTRESS (Figure c) experiments are strikingly similar. This demonstrates that the effects of surface heat and freshwater fluxes on EKE are small, although their impacts on ocean temperature and salinity are large (Li et al, ). In Regions 1, EKE is 6.6% enhanced in the NoSTRESS experiment compared with the NoISO experiment, and in Region 2, EKE is 8.6% stronger in NoISO than in NoSTRESS (Figure ).…”
Section: Contributions Of Wind Forcing and Oceanic Internal Instabilitymentioning
confidence: 97%
“…However, the EKE patterns in the NoISO (Figure b) and NoSTRESS (Figure c) experiments are strikingly similar. This demonstrates that the effects of surface heat and freshwater fluxes on EKE are small, although their impacts on ocean temperature and salinity are large (Li et al, ). In Regions 1, EKE is 6.6% enhanced in the NoSTRESS experiment compared with the NoISO experiment, and in Region 2, EKE is 8.6% stronger in NoISO than in NoSTRESS (Figure ).…”
Section: Contributions Of Wind Forcing and Oceanic Internal Instabilitymentioning
confidence: 97%
“…Modeling studies have shown that the coupled dynamics of the ocean‐atmosphere system, at timescales as short as the diurnal, strongly affect the structure and variability of the large‐scale tropical atmosphere (Fu et al, ; Inness & Slingo, ; Woolnough et al, ). Observations have further demonstrated the coevolution of the atmosphere and ocean in response to monsoon forcing in the Indian Ocean, including within the Madden‐Julian Oscillation (McPhaden & Foltz, ; Moum et al, , ), and during boreal summer intraseasonal oscillations (Li et al, ; Sengupta & Ravichandran, ). While sea surface temperature (SST) controls coupling at the air‐sea interface, SST is itself influenced by net atmosphere‐ocean heat flux, turbulent entrainment of typically cooler deep water into the mixed layer (ML), horizontal and vertical advection, and the ocean's mixed layer depth (MLD).…”
Section: Introductionmentioning
confidence: 98%
“…The definition of the barrier layer is the region between the base of the mixed layer to the bottom of the isothermal layer (Balaguru et al ., ). Also, it exhibits seasonal variation showing strong stratification (and thick barrier layer) in the post‐monsoon season and less stratification (thin barrier layer) in the pre‐monsoon season (Li et al ., ). Therefore, considering this fact, post‐monsoon TCs are relatively stronger than those in the pre‐monsoon season (Mohapatra et al ., ).…”
Section: Introductionmentioning
confidence: 99%